Experimental determination of high-acceleration shock characteristics of industrial marine fenders / David N. V., Adelin Khairina M. S. and Vipin Gopan - N. V., David; M. S., Adelin Khairina; Gopan, Vipin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Engineering systems are often subject to complex loading mechanisms including accelerated mechanical shock during transportation, handling, and operations. Shock can be understood as a drastic, irregular change in acceleration experienced by an object due to impact at a very short period. This paper presents a preliminary study of the crashworthiness properties of in-service industrial marine fenders (or bumpers) intended for shock energy absorption. The peak accelerations (Gpeak) of the test specimens are experimentally measured and compared to theoretical estimations. The energy absorptions and impact forces of the test specimens are calculated using analytical formulations. The effects of introducing tubular through-holes in the specimens on the resulting peak accelerations and thereby the shock energy absorbing capacities are also investigated. Test specimens of thicknesses ranging between 10 mm and 30 mm are subjected to half-sine shock waves between 50G and 70G, which are generated by dropping a 5-kg payload from different heights ranging from 150 mm to 280 mm onto a padded shock seat for a pulse duration between 5 and 8 ms. The analytically determined Gpeak agrees well with the experimental values. It is found that the through-holes specimens with lower Gpeak, resisted smaller impact forces and absorbed up to 12% lesser energy per unit mass than their solid counterparts.